High-Efficiency Switched-Capacitor Multilevel Inverter Topology With Lower Number of Switching Components - Atif Iqbal; Ahmed Awadelseed; Jaroslaw Guzinski (IEEE Access)
To increase the voltage from sources such as photovoltaic (PV) systems, fuel cells, and battery storage devices, a boost conversion is required. The proposed switched capacitor multilevel inverter (SCMLI) topology incorporates nine power semiconductor switches, a dual DC voltage source, and a single capacitor, capable of generating a nine-level output voltage with dual voltage gain. Additional features of the proposed SCMLI topology include self-voltage balancing of the capacitor without the need for any additional circuitry, reduced voltage stress across the switches, and an inherent capability for polarity reversal. Furthermore, the topology eliminates the need for bulky components like inductors, leading to a compact and cost-effective design. The performance of the proposed SCMLI is investigated through numerous simulation results under various operating conditions using PLECS software and validated using a laboratory prototype setup. The proposed SCMLI topology is further analyzed by integrating a solar PV system with a maximum power point tracking (MPPT) algorithm to ensure optimal power extraction. The system demonstrates excellent output voltage quality with low total harmonic distortion (THD), meeting the stringent requirements for power conversion in renewable energy applications. An efficiency of 96.3% is achieved at the rated power of 0.9 kW, confirming its potential for high-performance and sustainable energy conversion.